Dynamics of solitons and weakly ion-acoustic wave structures to the nonlinear dynamical model via analytical techniques - Bilal, Muhammad; Ren, Jingli; İnç, Mustafa; Alqahtani, Rubbayi T. T. (Springer, 2023)
This study employs the generalized exponential rational function method and ((G')/(G)2) -expansion function method. Computer algebra is used to study the multiple wave solutions to the (2+1)-dimensional nonlinear Zakharov-Kuznetsov modified equal-width problem. In the study of plasma physics, this model is utilized to represent the effects of a magnetic field on a weak ion-acoustic waves. Bright, dark, singular, and their combo forms solutions are extracted. Besides, the different kinds of the hyperbolic, trigonometric, rational, exponential function and singular periodic wave structures are also obtained. The parameter constraints for the existence of such solitons are also enumerated. With suitable parameter values, the results are shown and supported theoretically by visualizing 3D surface plots, 2D line plots, and corresponding contour graphs. The results of this research show that the methods used to improve the system's nonlinear dynamical behavior are effective. Intricate phenomena can now be analyzed with computational tools that are not only effective but also easy to use and compatible with one another. We believe that many engineering model professionals will find this work useful as well. Mathematica has been used to confirm the accuracy of these solutions for all retrieved results.
Keywords: Soliton solutions; (2+1)-Dimensional nonlinear ZK-MEW; GERFM; ((G')/(G)2)-Expansion